Optimizing Decentralization Of Education Through Regional Autonomy: Strategy And Implementation - Anastasya, Arum; Aditya Ramadhan, Aditya; Ramadhan, Aulia Fitriani (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
One of the efforts to improve the quality and equity of education services in Indonesia is to implement a decentralized approach. In this model, local governments are given greater responsibility in managing the education sector in their respective regions. The goal is for education policies and programs to be more aligned with local needs. This article will discuss how the decentralization strategy can be optimized in its implementation within the framework of regional autonomy. The results of the study using a qualitative approach show that the implementation of educational decentralization still faces several major obstacles, such as limited human resource capacity in the regions, weak coordination between the center and regions, and minimal allocation of the education budget. Data were obtained through literature studies by reviewing sources such as journals, books, and policy documents from the last five years. The analysis was conducted using content analysis techniques, highlighting important themes that emerged from the literature. These findings emphasize the need for strategies to strengthen managerial capacity, data-based planning, and synergy between institutions to support the success of educational decentralization.